The Nano-Based Catalyst for the Synthesis of Benzimidazoles - Keri, Rangappa S.; Adimule, Vinayak; Kendrekar, Pravin; Sasidhar, B. S. (Topics in catalysis, 2025)
The properties of benzimidazole and its derivatives have been studied over more than one hundred years. The benzimidazole ring is an important pharmacophore in modern drug discovery. Benzimidazole-based compounds possess potential application as medicinal drugs, presently; more than 20 drugs are available for the treatment of different diseases. Also, this motif is considered as privileged structure in medicinal chemistry because of its wide range of biological activities viz., antibacterial, antifungal, anticonvulsant, anti-tubercular, anti-HIV, anti-diabetic, anti-oxidant, anticancer, anti-inflammatory, analgesic antileishmanial, and antihistaminic agents etc. Owing to the diverse therapeutic applications, the incorporation of benzimidazole nucleus has become a field of high interest to organic and medicinal chemists. The various key starting materials (KSMs) utilized includes, aromatic and heteroaromatic 2-nitro-amines, phenylenediamine, carboxylic acids or its derivatives. However, these classical methods suffer from demerits such as, low atom economy, the formation of by-products, harsh reaction conditions, extended reaction period, expensive catalysts, and unsatisfactory yield of products as well as toxic solvents. Hence, the chemists have their attention towards developing synthetic processes primarily based on the set of principles of green chemistry. In this context, many efficient methods were developed for the synthesis of benzimidazole using the nanocatalyst or nanostructures. In this review, special emphasis has been given to discuss the “green” synthetic techniques adopted for the preparation of functionalized benzimidazole congeners as well as key mechanistic considerations and future outlook in this area. In this review, the literature up to the November 2021 in which very recently reported synthetic routes to access benzimidazole scaffolds are discussed. We are focused on, in particular, the synthetic methodologies/routes to construct 2-substituted/1,2-disubstituted benzimidazole or benzimidalones via various protocols involving condensation, cyclization, metal-free conditions, solvent-free conditions, and using nanocatalyst. This review will further aid the researcher to in developing more efficient and facile methods for the synthesis of benzimidazoles and associated hybrids. Graphical Abstract In this review, special emphasis has been given to discuss the “green” synthetic techniques adopted for the preparation of functionalized benzimidazole congeners as well as key mechanistic considerations and future outlook in this area. In this review, the literature up to the November 2021, in which very recently reported synthetic routes to access benzimidazole scaffolds are discussed. In particular, the synthetic methodologies/routes to construct 2-substituted/1,2-disubstituted benzimidazole or benzimidalones via various protocols involving condensation, cyclization, metal-free, solvent-free, and using nanocatalyst. This review will further aid the researcher in developing more efficient and facile methods for the synthesis of benzimidazoles and associated hybrids.